The mathematical contents teaching and learning from a communicative perspective - Pérez Ariza, Karel; Pérez Ariza, Karel; Hernández Sánchez, José Emilio; Coaguila Manero, Liliana Milagros (Transformación, 2024)
Objective: The paper aims at devising a didactic model for the treatment of mathematical contents, based on the assumption of learning as a process of textual comprehension and considering the texts as a cultural unit. Methods: Documentary analysis was used as an empirical method to construct the theoretical framework. Methods such analysis-synthesis, induction and deduction, and modeling were used from a functional, structural and systemic perspective to characterize the state of art and devise the proposal. Results: The proposed model is accompanied by a methodology, based on the resizing of the Mathematics lesson as a system of didactic components for the leadership of the processes of comprehension and production of meanings from mathematical texts (propositions, definitions and procedures). Conclusions: The effectiveness of the proposed model lays on the renew description of the Mathematics lesson components having the processes of comprehension and production of mathematics texts as a central axis.